Effect of Alkali and Alkaline Earth Metallic Species on Biochar Reactivity and Syngas Compositions during Steam Gasification - Yip, Kong; Tian, Fujun; Hayashi, J.; Wu, Hongwei (American Chemical Society, 2010)
Biochars were prepared from the pyrolysis of the wood, leaf, and bark components of mallee biomass in a fixed-bed reactor at 750 °C. The results show that the volatilization of inherent alkali and alkaline earth metallic (AAEM) species is 10−20% during the pyrolysis of raw wood, bark, and leaf samples. Acid treatment of the biochar samples was also carried out to prepare a set of acid-treated biochar samples. Although the majority of the inherent AAEM species were removed by acid-treatment, there are always some AAEM species that could not be removed for all biochars. Steam gasification experiments of both the raw and acid-treated biochar samples were carried out in a fixed-bed reactor at 750 °C and a steam concentration of 8.2 vol %. Data on the instantaneous syngas composition were obtained as a function of biochar conversion during steam gasification. Our data illustrated the importance of, in the study of steam gasification reaction mechanisms and kinetics of solid fuels such as biochars, optimizing the reaction conditions to minimize steam consumption so that the steam partial pressure in the reactor is kept reasonably constant during the whole course of gasification.The results indicate that Na, K, and Ca retained in the biochars are the key catalytic species, with the catalytic effect appearing to be in the order K > Na > Ca during the steam gasification reaction of these biochars. During steam gasification, almost all of the inherent AAEM species in biochar are retained in the reacting biochar, throughout the course of conversion. Steam gasification of both the raw and acid-treated biochars produces high-quality syngas products that contain little methane. Further analysis shows that during the course of biochar conversion, the primary gasification product is most likely CO, and overall the water-gas-shift reaction is primarily responsible for the CO2 formation. It is found that the inherent AAEM species, although catalyzing the biochar gasification significantly, appear to have insignificant catalytic effect on the water-gas-shift reaction under the current gasification conditions.